Novel planar wire-grid antenna arrays for automotive radars operating at 77 GHz - Helaly, Hossam (AUC Knowledge Fountain, 2020)
Automotive radars are the critical components for future driving assistance technologies. Nowadays, their usage is a constraint on the premium segment automobiles; however, there are intensive studies to facilitate these technologies to the lower segment. The main challenges that face automakers to develop new automotive radars are fabrication cost, compactness, bandwidth, and radiation properties. This research focuses on developing a novel class of planar antenna arrays, which operate at a frequency of 77 GHz. The proposed arrays can be fabricated using multilayered cheap printed circuit board lamination technology. The proposed antennas are arrayed using mixed wire-gridding and corporate arraying techniques, which leads to compactness. They show good radiation characteristics and frequency response. Being planar, they can be easily integrated with the driving electronic circuits. All antenna designs are simulated and optimized using ADS/Momentum solver. This full-wave electromagnetic solver is suitable for analyzing electrically large planar antennas, as it is based on the formulation of the integral equations solved using the method of moments. The results are cross-validated using CST Microwave Studio. Good agreement is observed. The masks needed for realizing the proposed arrays are prepared and already sent for fabrication.